Feasibility of creating an island divertor in the Uragan-2M torsatron - Lesnyakov, G.G.; Shapoval, A.N.; Pavlichenko, O.S. (Вопросы атомной науки и техники, 2012)
The concept of an island divertor appears the only suitable idea that may be helpful to make up for the absence of a natural helical divertor in the magnetic configuration. In this context, the paper presents and discusses the measured and calculated magnetic surface structures of different configuration modes, where large magnetic islands or their remains at the edge of the plasma volume may be used for experimental implementation of the island divertor.